2021
DOI: 10.1186/s13063-021-05869-3
|View full text |Cite
|
Sign up to set email alerts
|

TANGO: effect of tango Argentino on cancer-associated fatigue in breast cancer patients—study protocol for a randomized controlled trial

Abstract: Background The majority of breast cancer patients suffer from persistent impairments after completion of their primary oncological therapy. Cancer-related fatigue (CRF) in particular is a multidimensional syndrome having a profound negative impact on the quality of life. To counter CRF symptoms, physical activities are suggested as first-line interventions, mind-body therapies have been shown to be effective, and music therapy can also reduce anxiety and stress in breast cancer patients. Tango … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Besides, different forms of dance are under consideration for therapeutic use for breast cancer patients with CRF [23,24]. Also, apart from group therapy, DMT has been utilised as an individualised therapy in a few studies [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, different forms of dance are under consideration for therapeutic use for breast cancer patients with CRF [23,24]. Also, apart from group therapy, DMT has been utilised as an individualised therapy in a few studies [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…This clinical trial was an investigator-initiated trial approved by the responsible local ethics committee (Ethik-Kommission der Ärztekammer Berlin, on 2 April 2020 with the reference number Eth-05/20) and has been registered (trial registration number DRKS00021601). The study protocol was published [24]. All eligible participants provided written informed consent for their participation in the study before enrollment, and the trial was reported in compliance with the Consolidated Standards of Reporting Trials (CONSORT) reporting guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed methods of the TANGO trial have been reported and published in the study protocol [24]. Briefly, the TANGO trial was a single-center, 2-arm, randomized controlled clinical trial conducted at the Research Institute Havelhöhe gGmbH at the Hospital Gemeinschaftskrankenhaus Havelhöhe, Berlin, Germany.…”
Section: Participants Study Design and Proceduresmentioning
confidence: 99%
“…Here, we conducted a real-world data (RWD) study by longitudinal evaluation of the tango trial [19] and the oncological patient registry data from Network Oncology (NO) [20]. The tango trial was an investigator initiated trial, and the study protocol and results were published [19,21]. The NO study and the tango trial were approved by the responsible local ethics committee (Ärztekammer Berlin) and registered (Trial registration numbers DRKS00013335 and DRKS00021601).…”
Section: Methodsmentioning
confidence: 99%
“…For a control cohort, NO breast cancer survivors who were diagnosed with stage I to III breast cancer and reported increased fatigue symptoms (CFS-D total > 23) at the one-year follow-up were included. The participants of the tango trial were recruited between June 2020 and May 2022 according to the published study-protocol [21] and received the six-week tango program, as described in detail [19]. Demographic, behavioral, and medical information of the tango cohort were collected with clinical interviews, self-reported fatigue, and QoL questionnaires were surveyed prior to, after the intervention, and six, and twelve months thereafter.…”
Section: Participants Study Design and Proceduresmentioning
confidence: 99%